MODERN TRENDS IN TRANSLATION STUDIES - Ali Abdel-Zaher Abu Amra, (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
Over recent decades, translation has transformed from a purely linguistic activity into a multidisciplinary scientific field. It is no longer confined to individual translators’ efforts or traditional linguistic analysis; rather, it has expanded into the horizons of the knowledge and technological revolution to keep pace with rapid developments and major leaps driven by artificial intelligence, as well as modern studies and theories that influence the shaping of the world’s image across languages. The forms of translation have also diversified to include audiovisual translation, machine translation, specialized simultaneous interpreting, and other types.